PENERAPAN PENURUNAN NILAI INSTRUMEN KEUANGAN BERDASARKAN PSAK 50 DAN 55 (REVISI 2006) DAN PERUBAHAN YANG HARUS DILAKUKAN PERUSAHAAN - Rizka Annisa (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
Convergence between US GAAP and IFRS certainly affect to accounting standard that occur now in Indonesia. Indonesia is harmonizing with IFRS and revising several standards so that it will comply with International Standard. One of the standard that being revised is PSAK 50 (Presentation and Disclosure of Financial Instrument) and PSAK 55 (Recognition and Measurement of Financial Instrument). Along with harmonization and applying fair value accounting, financial instrument need to be assessed to their market value if there is descent of the value, the financial instrument need to be impaired. With applying PSAK 50 and 55 (revision 2006), the impairment process should be supported by reliable, documented data, and need another data to prove that the value of financial instrument is descent. Company has to prepare themself to face the changes that happened, which is changes in information system, organization, technology and human resource. In addition, company should understand overall of PSAK 50 and PSAK 55, because there is a lot of detailed rules in this revision.